Convergence of weighted sums for sequences of pairwise NQD random variables. Issue 20 (17th October 2016) - Wu, Yongfeng; Guo, Mingle
ABSTRACT: The authors discuss the convergence for weighted sums of pairwise negatively quadrant dependent (NQD) random variables and obtain some new results which extend and improve the result of Bai and Cheng(2000) . In addition, we relax some restrictions of the conditions in their result. Some new methods are used in this article which differ from that of Bai and Cheng(2000) .